An Optimal Control Problem for a Generalized Boussinesq Model: The Time Dependent Case - Boldrini, Jose Luiz; Fernández-cara, Enrique; Rojas-medar, Marko Antonio (Revista Matemática Complutense, 2007)
We consider an optimal control problem governed by a system of nonlinear partial differential equations modelling viscous incompressible flows submitted to variations of temperature. We use a generalized Boussinesq approximation. We obtain the existence of the optimal control as well as first order optimality conditions of Pontryagin type by using the Dubovitskii-Milyutin formalism.